Technology convergence and the consumption intention in the automotive sector: a netnographic research - Emilio José Montero Arruda Filho; Luis Augusto Molina Alexandroni (Revista Eletrônica de Ciência Administrativa, 2021)
The technological convergence scenario represented by the connection of the user's cell phone to the sound system, the availability of a GPS and maneuvering camera on the dashboard car brings a perception of multifunctionality to the decision process of buying new cars. The objective of this research was to understand whether technological factors influence consumption intent in the Brazilian automobile market, when mediated by the perceived values of the product. The research method was qualitative (netnography) with the aid of a tool of Big Data. It was made a survey of these motivational factors and it was observed that in the intentions of consumption the ones that are present are the hedonic, utilitarian and social values, through characteristics like pleasure in driving, appreciation by technology, economy, rationality in the purchase decision, extension of personality (extended self) and affirmation of personality towards the social group. It was also verified the devotion to the product and/or manufacturer represented by characteristics such as passion, dream of consumption and appreciation of the differentials of the automobile. The data analyzed were the comments posted on Facebook from Fiat, Ford and Volkswagen. It was also observed the presence of negative categories related to the motivation for the consumption as the fear to consume and the frustrated expectation after the purchase.